PATHOLOGICAL CHANGES IN BLOOD CELLS IN HERBICIDE POISONING - Siddiqova Amina; Xaydarova Shaxrizoda; Sotimova Shohida (TADQIQOTLAR, 2025)
Abstract The aim of this work was to elucidate the structural bases of the reaction of blood system cells in acute and chronic herbicide poisoning and to find spores for their correction with metal-containing biocomplexes. Based on the goal, the following tasks  were  set:  -to  study  the  morphofunctional  state  of  various  (copper-containing cobalt) biocomplexes on the morphofunctional state of the cells of the blood system in acute and chronic herbicide poisoning.